Linguistic ethnography collecting, analysing and presenting data - Copland, Fiona 1962-; Creese, Angela; Rock, Frances 1974-; Shaw, Sara (SAGE, 2015)
"This is an engaging interdisciplinary guide to the unique role of language within ethnography. The book provides a philosophical overview of the field alongside practical support for designing and developing your own linguistic ethnographic research. It demostrates how to build and develop arguments and engages with practical issues such as ethics, transcription and impact. There are chapter-long case studies based on empirical research that will explain key themes and help you collect and analyse your own linguistic data. Drawing on the author's experience, they outline the practical, epistemological and theoretical decisions that researchers must take when planning and carrying out their studies"--Back cover.